Metodyczne aspekty oceny efektywności gospodarowania w rolnictwie - Ziętara, Wojciech (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
Author of the paper made distinction between agricultural holding and agricultural enterprise what is crucial for the purpose of evaluation of economic efficiency in agriculture. Agricultural holding is an economic unit separated according to organizational structure, constituting combination of three production factors: land, labour and capital and aiming for farm production. On the contrary,agricultural enterprise in addition has economically and legally separated status. It is functioning as an independent economic unit and aiming for agricultural production and services for sale. In case of agricultural holding - in opposition to enterprise - both ownership structure and sources of financing are not taken into consideration, therefore to evaluate its business performance dissimilar categories (production) should be used to agricultural enterprise (income, profit).